Predominance of III/ST19 and Ib/ST10 Lineages With High Multidrug Resistance in Fluoroquinolone-Resistant Group B Streptococci Isolates in Which a New Integrative and Conjugative Element Was Identified - Gao, Kankan; Gao, Chunyan; Huang, Lianfen; Guan, Xiaoshan; Ji, Wenjing; Chang, Chien-Yi; McIver, David J.; Deng, Qiulian; Zhong, Huamin; Xie, Yongqiang; Deng, Lei; Gao, Fei; et al. (Frontiers in Microbiology, 2021)
Fluoroquinolone (FQ)-resistant Group B Streptococcus (GBS) has been reported with considerable cross-resistance, worsening the crisis of multidrug resistant (MDR) GBS in clinical settings. However, national epidemiological data on FQ-resistant GBS in mainland China have not been well characterized. This study aimed to determine the prevalence of FQ-resistance among GBS from neonatal invasive infections and maternal colonization in northern and southern China, to investigate the serotyping, multi-locus sequence typing, and antibiotic cross-resistance, and to characterize the mutations in gyrA and parC genes in quinolone resistance-determining region (QRDR). In order to provide a comprehensive view of location and structure of resistance genes, whole-genome sequencing on III/ST19 MDR isolates were performed. Among 426 GBS, 138 (32.4%) were FQ-resistant, with higher prevalence in northern China than southern China in both neonates (57.8%, 37/64 versus 21.7%, 39/180) and pregnant women (50.9%, 29/57 versus 26.4%, 33/125). Serotypes were distributed as III (48.5%), Ib (39.9%), V (6.5%), and Ia (5.1%). Sequence types were mainly ST19 (53.6%) and ST10 (39.1%), followed by ST12 (1.4%), ST17 (1.4%), ST23 (1.4%), and 0.7% each of ST27, ST188, ST197, and ST597. ST19 isolates were more prevalent in southern China than northern China in both neonates (64.1%, 25/39 versus 27.0%, 10/37) and pregnant women (81.8%, 27/33 versus 41.4%, 12/29), whereas ST10 isolates were more common in northern China than southern China in both neonates (64.9%, 24/37 versus 20.5%, 8/39) and pregnant women (58.6%, 17/29 versus 15.2%, 5/33). Serotype III isolates were mainly ST19 (89.6%, 60/67) while Ib isolates were largely ST10 (94.5%, 52/55). Sequencing data revealed several mutations in QRDR, including Ser81Leu in gyrA (99.2%, 130/131), Ser79Phe or Tyr in parC (76.2%, 48/63), and a previously unreported Ile218Thr and Ile219Phe double mutation pattern (49.2%, 31/63) in parC. ST10 isolates were associated with Ser79Phe (84%, 21/25) while ST19 isolates were limited to Ser79Tyr (95.7%, 22/23). A new integrative and conjugative element (ICE) harboring tetM and gyrA genes was identified in a III/ST19 isolate. This study investigates the molecular characteristics of FQ-resistant GBS in northern and southern China, emphasizing the need for continuous surveillance geographically and further research to characterize the mechanisms of ICE transfer.